Renewable energy public-private partnership projects in Egypt: Perception of the barriers and key success factors by sector - Kareem Othman; Rana Khallaf (Alexandria Engineering Journal, 2023)
Given its location, Egypt has a tremendous potential for renewable energy resources such as wind, solar, and hydropower. On the other hand, renewable energy projects require huge upfront costs which makes it difficult for the Egyptian government to fulfill. Thus, renewable energy projects in Egypt are conducted in the form of public–private partnership (PPP) projects to take advantage of the private entity’s financial support. Thus, this study focuses on studying and analyzing renewable energy PPPs in Egypt using a questionnaire survey. First, the main barriers and keys success factors (KSFs) were identified by collecting previous studies in the area to build the survey. The survey was then created and disseminated to experts involved in renewable energy PPPs in Egypt. A total of 25 responses were collected from experts in the public and private sectors. The results show that the main barriers for renewable energy PPPs in Egypt are regulatory and political barriers, while well prepared contact documents and skilled and efficient parties are the main KSFs. Additionally, the different sectors perceive the barriers and KSFs differently. Finally, the results show that unlike the public sector, the private sector is efficient in identifying and valuing risks appropriately.